Enriching the hierarchical model of achievement motivation: Autonomous and controlling reasons underlying achievement goals. (23rd September 2014) - Michou, Aikaterini; Vansteenkiste, Maarten; Mouratidis, Athanasios; Lens, Willy
<x xml:space="preserve">Abstract</x> Background The hierarchical model of achievement motivation presumes that achievement goals channel the achievement motives of need for achievement and fear of failure towards motivational outcomes. Yet, less is known whether autonomous and controlling reasons underlying the pursuit of achievement goals can serve as additional pathways between achievement motives and outcomes. Aims We tested whether mastery approach, performance approach, and performance avoidance goals and their underlying autonomous and controlling reasons would jointly explain the relation between achievement motives (i.e., fear of failure and need for achievement) and learning strategies (Study 1). Additionally, we examined whether the autonomous and controlling reasons underlying learners' dominant achievement goal would account for the link between achievement motives and the educational outcomes of learning strategies and cheating (Study 2). Sample Six hundred and six Greek adolescent students (Mage = 15.05, SD = 1.43) and 435 university students (MageM = 20.51, SD = 2.80) participated in studies 1 and 2, respectively. Method In both studies, a correlational design was used and the hypotheses were tested via path modelling. Results Autonomous and controlling reasons underlying the pursuit of achievement goals mediated, respectively, the relation of need for achievement and fear of failure to aspects of learning outcomes. Conclusion Autonomous and controlling reasons underlying achievement goals could further explain learners' functioning in achievement settings.